THE RELATIONSHIP BETWEEN MANAGEMENT SUPPORT, TRAINING MOTIVATION, INTENTION TO TRANSFER, AFFECTIVE REACTION, UTILITY REACTION, SUPERVISOR SUPPORT, AND LEVEL III AND IV LEADERSHIP TRAINING TRANSFER: A CASE IN INDONESIAN MINISTRY OF FINANCE - Ubed, Roby Syaiful (Polytechnic of State Finance STAN, 2016)
The purpose of this research is to examine how training transfer is influenced by management support, training motivation, intention to transfer, affective reaction, utility reaction, supervisory support. To achieve this purpose, this study used the employees in Indonesian Ministry of Finance. A sample of 258 employees from level III and level IV leaders completed questionnaires that include measurements such as training motivation, supervisor supports, affective reaction, utility reaction, intention to transfer, training transfer, perceived training transfer, training retention, managerial transfer support, motivation to learn, training self-efficacy, and demographic characteristics. Hypothesis testing was done by using three steps of hierarchical regression analysis. The results of this study indicate that there are significantly positive relationships between the aforementioned independent variables and training transfer. Implications of this study were discussed.Â